Lampedusa, football and COVID-19: transitions at the border and the role of sport. Issue 1 (1st January 2023) - Norrito, Alessio; Mason, Carolynne
ABSTRACT: Lampedusa is a remote Italian island, known as a border zone and European point of entry for many asylum-seekers coming by boat from North Africa. This research seeks to understand the value of sport in Lampedusa for its local and migrant population, in the context of the global COVID-19 pandemic. Data were collected through semi-structured interviews with experts from the local community. Results show that sport in Lampedusa is often synonymous with football. Football has always been informally practiced in the island but has proved to be of practical social value to both asylum-seekers and the local population. The pandemic has however interrupted the playful interactions occurring between asylum-seekers and the local youth. Findings show that the interactions and connections enabled through football can be fundamental for asylum-seekers to find direction in their journey but since the start of the pandemic, these interactions have become limited, and serve exclusively as temporary moments of relief. These changes have also impacted the local population, anxious about the transition occurring within the COVID-19 pandemic, resulting in worries about the condition of the asylum-seeking population who are proceeding in their European journey without the assistance of the locals.